2013
DOI: 10.1007/s10517-013-2150-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Phenazepam on the Behavior of C57Bl/6 and BALB/c Mice in the Open Field Test after Naloxone Pretreatment

Abstract: We studied the effects of phenazepam (0.075 mg/kg) after pretreatment (5 minutes before) with naloxone (10 mg/kg) on open-field behavior of C57Bl/6 and BALB/c mice. In ex vivo experiments, we studied the effects of naloxone (1 and 10 mg/kg) on receptor binding of [(3)H]-flunitrazepam by membranes of brain fraction (P1+P2) of C57Bl/6 and BALB/c mice. It was shown that naloxone increased motor activity in the open field in BALB/c mice and decreased this parameter in C57Bl/6 mice. During combined treatment, nalox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
2
4
0
Order By: Relevance
“…The results of open-field test indicate that GGRE, NS1619, IbTX had no significant effect on the mice's locomotor system. Results of previous studies was similar to our study results (Seredenin et al, 2013). In our study, morphine caused a decrease in mice's motor activity and anxiety, which is similar to the results of a previous study (Wang et al, 2017).…”
Section: Boletín Latinoamericano Y Del Caribe De Plantas Medicinales Y Aromáticas / 480supporting
confidence: 93%
See 1 more Smart Citation
“…The results of open-field test indicate that GGRE, NS1619, IbTX had no significant effect on the mice's locomotor system. Results of previous studies was similar to our study results (Seredenin et al, 2013). In our study, morphine caused a decrease in mice's motor activity and anxiety, which is similar to the results of a previous study (Wang et al, 2017).…”
Section: Boletín Latinoamericano Y Del Caribe De Plantas Medicinales Y Aromáticas / 480supporting
confidence: 93%
“…In our study, morphine caused a decrease in mice's motor activity and anxiety, which is similar to the results of a previous study (Wang et al, 2017). The present study showed that the effects of the morphine were reversed by naloxone, consistent with the results reported in the literature (Seredenin et al, 2013). Since systemic administration of NS1619 does not readily cross the blood-brain-barrier, NS1619 might not cause anxiety or impair motor activity (Lu et al, 2014).…”
Section: Boletín Latinoamericano Y Del Caribe De Plantas Medicinales Y Aromáticas / 480supporting
confidence: 92%
“…We used a 30-minute interval between drug administration and behavioral testing based on published protocols (Angrini et al, 1998;Birkett et al, 2011;Choleris et al, 2001;Heredia et al, 2013a;Lalonde and Strazielle, 2010;Salomons et al, 2012;Seredenin et al, 1990Seredenin et al, , 2013. Our PK studies determined that peak CDP concentration occurred prior to testing.…”
Section: Discussionmentioning
confidence: 99%
“…The open field test is a well-known test for behavioral analysis, which has been used for several decades [ 21 , 22 ]. Even though the test is not absolutely specific, it is a good tool to quantify well-being [ 23 , 24 ]. In former analyses, we could already demonstrate the usability of the test to evaluate well-being in PDAC [ 11 , 25 ].…”
Section: Methodsmentioning
confidence: 99%